2014
DOI: 10.1186/1479-7364-8-8
|View full text |Cite
|
Sign up to set email alerts
|

QGRS-Conserve: a computational method for discovering evolutionarily conserved G-quadruplex motifs

Abstract: BackgroundNucleic acids containing guanine tracts can form quadruplex structures via non-Watson-Crick base pairing. Formation of G-quadruplexes is associated with the regulation of important biological functions such as transcription, genetic instability, DNA repair, DNA replication, epigenetic mechanisms, regulation of translation, and alternative splicing. G-quadruplexes play important roles in human diseases and are being considered as targets for a variety of therapies. Identification of functional G-quadr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 70 publications
0
37
0
Order By: Relevance
“…The significant enrichment of PQSs in many viruses with respect to the corresponding randomized genomes is an indication that the clustering of G-islands did not occur by pure chance, suggesting a specific biological role of the G4 structures [40]. Complementary to this, the analysis of the PQS conservation highlights every PQS that is conserved among viral strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant enrichment of PQSs in many viruses with respect to the corresponding randomized genomes is an indication that the clustering of G-islands did not occur by pure chance, suggesting a specific biological role of the G4 structures [40]. Complementary to this, the analysis of the PQS conservation highlights every PQS that is conserved among viral strains.…”
Section: Discussionmentioning
confidence: 99%
“…Then, we evaluated the conservation of PQSs among different strains of each viral species, hypothesizing that the presence of a conserved PQS within a less conserved genome environment could be an indication of a G4 with a biological function [40]. To allow for the evaluation of PQS conservation in the local context of viral genomes, we computed the "G4 scaffold conservation index" (G4_SCI) for each PQS in each virus species.…”
Section: Detection Of G4 Patterns In All Known Human Virusesmentioning
confidence: 99%
“…Only a few studies have investigated the evolutionary conservation of G-quadruplexes, and none have used sequence models that allow non-canonical tetrads (6365). Analysis of the human genome using these improved sequence models revealed that, in some cases, G-quadruplexes with GTP-binding and peroxidase activity have been conserved in evolution.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of high resolution sequencing-based methods > 716,000 G4 structures were identified, where ∼451,000 were not predicted by computational methods 17,18 . These sequences are highly conserved in mammals, with limited conservation in evolutionarily lower organisms 19,20 . Genome-wide searches using G-quadruplex-specific probes and structure-based pull-down strategies have revealed that the pG4 sequences are not randomly distributed, being enriched at telomeres, promoter regions and replication origins 9,21 .…”
Section: Dna G-quadruplexesmentioning
confidence: 99%